Penyuluhan Inovatif tentang Penggunaan dan Waktu Konsumsi Obat: Pengabdian Masyarakat di Desa Kamal, Sumatera Selatan - Mauritz Pandapotan Marpaung; Berkah Mutiara; Putri Picaso Azury Sheva; Dendi Bianda Saputra; Imam Saputra; Shely Junian Permata; Sania Kolopaking; Dian Oktarina; Marsya Reskiani Lole; Martina Vevi Yanti; Amelia Ramadhani; Muhammad Afriansyah; Suparwatini Suparwatini; Juwita Indah Sari; Ira Sagita; Mariansari Mariansari (JURNAL PENGABDIAN KADER BANGSA, 2025)
Proper drug use, especially regarding the timing of consumption, is an important aspect of rational and effective therapy. Unfortunately, the rural community's understanding of the right time to take medicine is still low, which can affect the success of treatment. This community service activity was carried out in Kamal Village, Ogan Ilir Regency, South Sumatra, with the aim of increasing the knowledge and awareness of the community regarding the correct timing of drug consumption. The methods used in this activity include direct counseling through educational lectures, simulations, leaflet distribution, and interactive discussions with residents and village health cadres. Evaluation was conducted using a simple pre-test and post-test to assess the improvement of participants' knowledge. The evaluation results showed a significant increase in understanding, from an average pre-test score of 64% to 92% in the post-test. In addition to increasing understanding, this activity also succeeded in raising community awareness to be more critical and active in asking health workers about the timing of drug consumption. The advantages of this activity are its participatory and community-based approach, although there are obstacles such as limited visual aids and uneven accessibility of participants. Overall, this counseling was effective in improving health literacy related to drug use in the village community.